2022
DOI: 10.1017/pasa.2022.15
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the radio emission of the core and host galaxy properties in Fanaroff–Riley type II radio galaxies

Abstract: We study the radio power of the core and its relation to the optical properties of the host galaxy in samples of high-excitation (HERG) and low-excitation (LERG) Fanaroff–Riley type II (FRII) radio galaxies. The radio galaxy sample is divided into two groups of core/non-core FRII, based on the existence of strong, weak or lack of single radio core component. We show that FRII LERGs with radio emission of the core have significantly higher [O III] line luminosities compared to the non-core LERG FRIIs. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…The lack of correlation could be due to the uncertainties exposed by AGN duty cycles. The result is also consistent with the result from Mazoochi et al (2022) for the core and noncore FRIIs. They showed that FRIIs with luminous radio core have on average higher [O III] luminosity than noncore or weak-core FRIIs.…”
Section: Relation Between [Oiii] Luminosity and Radio Properties Of Agnsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of correlation could be due to the uncertainties exposed by AGN duty cycles. The result is also consistent with the result from Mazoochi et al (2022) for the core and noncore FRIIs. They showed that FRIIs with luminous radio core have on average higher [O III] luminosity than noncore or weak-core FRIIs.…”
Section: Relation Between [Oiii] Luminosity and Radio Properties Of Agnsupporting
confidence: 91%
“…Core radio emissions have also been investigated for the extended sources (Baldi et al 2015(Baldi et al , 2019. Mazoochi et al (2022) investigate core and total radio emissions for a sample of FRII radio galaxies. They show that there is a correlation for FRII LERGs and HERGs when total radio luminosity has been considered.…”
Section: Relation Between [Oiii] Luminosity and Radio Properties Of Agnmentioning
confidence: 99%
“…To correct this effect, we need to find the contribution of beamed sources, which is different in each catalog. Mazoochi et al (2022) have discussed it for a sample of FRIIs selected from the catalog provided by Miraghaei & Best (2017). They showed that even for the core of FRIIs (compact component), beamed sources constitute 6%-30% of the sample.…”
Section: Resultsmentioning
confidence: 99%